Correlation Between Diabetes Mellitus and Clinical Outcome of Patients with Acute Coronary Syndrome Underwent Percutaneus Coronary Intervention Therapy in Dr Soetomo Surabaya Hospital - Alanna Sari Pratikto; I Gde Rurus Suryawan; Andrianto; Purwo Sri Rejeki (Universitas Airlangga, 2020)
Introduction: Coronary heart diseases continue to be the rising cause of mortality amongst Indonesian population, alongside with the increasing number of diabetic patients. The first line management of ACS is percutaneous coronary intervention (PCI), however previous have shown that diabetic patients have worse outcomes after therapy compared to non-diabetic patients. This study aims to compare the clinical outcomes between acute coronary syndrome (ACS) patients with diabetes and those without diabetes following percutaneus coronary intervention therapy. Methods: This study used cross sectional observational approach collecting records of ACS patients that underwent percutaneous coronary intervention in RSUD Dr Soetomo Surabaya from January 2018 to December 2019. Data regarding a patient’s age, gender, diabetic status, location of lesion, revascularization status, and clinical outcome were collected. Those with missing or incomplete data were excluded from the study. A total of 55 patients were included and analyzed, Results: amongst 55 patients that underwent PCI observed, 23 were diabetic and 32 were non-diabetic. Study has shown that diabetic patients have higher mortality rate compared to those without diabetes (6 patients vs. 1 patient, p=0,072) however based on the result analysis the p value of >0,05 showed no significant relationship between patients’ diabetic status and the clinical outcome following PCI therapy. Study has also shown that diabetic patients are more likely to undergo staged PCI (56,5%), than total revascularization PCI. Conclusion: Study has found that diabetic ACS has a higher mortality rate compared to those without diabetes, however analitycal studies found no significant relationship between the two variables. Further studies should be performed with higher number of patients to accurately investigate the relationship between diabetes melitus and PCI outcomes.